AKTIVITAS ANTELMINTIK BIJI Veitchia merrillii TERHADAP Ascaridia galli SECARA IN VITRO - Abdullah Hamzah; Muhammad Hambal; Ummu Balqis; Darmawi Darmawi; Maryam Maryam; Rosmaidar Rosmaidar; Farida Athaillah; Muttaqien Muttaqien; Azhar Azhar; Ismail Ismail; Rastina Rastina; Eliawardani Eliawardani (Majalah Obat Tradisional, 2016)
The objective of this research was to evaluate the anthelmintic activity of ethanolic extract of nuts Veitchia merrillii against intestinal nematode, Ascaridia galli. Phytochemical tests were performed for testing different chemicals group present in the extract. The effect of these extract were determined by in vitro based on inhibition of motility and mortality of worms. Amount of four worms were exposed in triplicate to each of phosphate buffered saline, 25 mg/mL, and 75 mg/mL crude ethanolic extract of V. merrillii, and 15 mg/mL albendazole. The motility of worm was observed on 9, 18, 27, and 36 hours interval. The mortality of worms were recognized by their straight flat appearance with no movements at the head and tail regions of the body. We found that the ethanolic extract of V. merrillii contains tannins, alkaloids, flavonoids, triterpenoids, and saponins neither steroid. Based on the in vitro trials conducted using above extract at 25 and 75 mg/mL concentration, the extract of V. merrillii showed anthelmintic effect. The extract of V. merrillii was effective at 75 mg/mL concentration only. The study indicated that it is potential to develop herbal-based anthelmintic to control A. galli in poutry.